Expression Pattern of Early Transcription Factors in Porcine Oocytes and Embryos - So Yeon Kim; Tao Lin; Joo Bin Lee; Jae Eun Lee; Hyun Young Shin; Dong Il Jin (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Many transcription factors are involved in directing the growth of porcine oocytes. The localization and expression level of a given transcription factor often differ at each stage of early embryonic growth, which spans from fertilization to the formation of the blastocyst. A hallmark of the blastocyst stage is the separation of the endodermal and mesodermal ectoderm. The embryo's medium and its effects are known to be crucial during early development compared to the other developmental stages, and thus require a lot of caution. Therefore, in many experiments, early development is divided into the quality of oocyte and cumulus cells and used in experiments. We thought that we were also heavily influenced by genetic reasons. Here, we examined the expression patterns of five key transcription factors (CDX2, OCT4, SOX2, NANOG, and E-CADHERIN) during porcine oocyte development whose expression patterns are controversial in the pig to the literature. Antibodies against these transcription factors were used to determine the expression and localization of them during the early development of pig embryos. These results indicate that the expressions of key transcription factors are generally similar in mouse and pig early developing embryos, but NANOG and SOX2 expression appears to show species-specific differences between pig and mouse developing embryos. This work helps us better understand how the expression patterns of transcription factors translate into developmental effects and processes, and how the expression and localization of different transcription factors can crucially impact oocyte growth and downstream developmental processes.